Montealtosuchus arrudacamposi, a new peirosaurid crocodile (Mesoeucrocodylia) from the Late Cretaceous Adamantina Formation of Brazil - de Souza Carvalho, Ismar; de Vasconcellos, Felipe Mesquita; Tavares, Sandra Aparecida Simionato (Zootaxa, 2007)
We describe a new species of Peirosauridae (Crocodyliformes, Mesoeucrocodylia), Montealtosuchus arrudacamposi gen. nov. et sp. nov., from the Late Cretaceous (Turonian-Santonian) strata of the Bauru Basin, Brazil. Montealtosuchus was found at the outskirts of Monte Alto County in reddish sandstones of the Adamantina Formation. This specimen is exquisitely preserved with skull, mandible, postcranial and exoskeletal elements in articulation that provides critical information of the anatomy of this group. The occurrence of Peirosauridae in the Adamantina Formation (Turonian-Santonian) widens the chronostratigraphic range of this Mesoeucrocodylia taxon in Brazil. Recent analysis suggests that the Peirosauridae is restricted to the Late Cretaceous deposits of South America.